1979
DOI: 10.1088/0031-9155/24/2/015
|View full text |Cite
|
Sign up to set email alerts
|

The gastrointestinal absorption of plutonium and americium in the hamster

Abstract: Plutonium-239 and americium-241 were administered to adult hamsters in various chemical forms and their absorption from the gut was measured. The results have been compared with published data on other species in order to derive values for the estimated absorption of these actinides in man. On the basis of current knowledge, the best values for adults would appear to be: 0.05% for americium, 0.01% for plutonium ingested in soluble form, and 0.0001% for plutonium ingested as the dioxide. Plutonium dioxide shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Analysis here (assuming s s = 10 −4 d −1 ) for a freshly prepared americium oxide gave f r = 0.6 and s r = 1 d −1 (giving assignment to Type M) for particles of size <0.025 µm, f r = 0.9, and s r = 4 d −1 (giving assignment to Type F) for particle size range 0.025–1.2 µm. For an AmO 2 suspension aged for 4 months in water, analysis here gave f r = 0.9 and s r = 3 d −1 for particles of size <0.025 µm, and f r = 0.7 and s r = 3 d −1 for particles in the size range 0.025–1.2 µm, giving assignment to Type M. (901) Stather et al. (1979a,b,c) studied clearance from the lungs of hamsters after inhalation of actinide oxides, either alone or in combination with other metals.…”
Section: Americium (Z = 95)mentioning
confidence: 74%
See 3 more Smart Citations
“…Analysis here (assuming s s = 10 −4 d −1 ) for a freshly prepared americium oxide gave f r = 0.6 and s r = 1 d −1 (giving assignment to Type M) for particles of size <0.025 µm, f r = 0.9, and s r = 4 d −1 (giving assignment to Type F) for particle size range 0.025–1.2 µm. For an AmO 2 suspension aged for 4 months in water, analysis here gave f r = 0.9 and s r = 3 d −1 for particles of size <0.025 µm, and f r = 0.7 and s r = 3 d −1 for particles in the size range 0.025–1.2 µm, giving assignment to Type M. (901) Stather et al. (1979a,b,c) studied clearance from the lungs of hamsters after inhalation of actinide oxides, either alone or in combination with other metals.…”
Section: Americium (Z = 95)mentioning
confidence: 74%
“…(1979b, 1984). For both species, the amounts of 239 Pu deposited in tissues from blood were <0.1% ILD at 30 d and <0.4% ILD at the end of the study (360 or 540 d; Stather et al., 1979a). Analysis here gave f r <10 −4 and s s = 5 × 10 −6 d −1 , with assignment to Type S. (765) Lataillade et al.…”
Section: Plutonium (Z = 94)mentioning
confidence: 92%
See 2 more Smart Citations
“…In vivo studies have shown intestinal absorption of particles to be size‐dependent, with smaller particles (polystyrene microspheres, colloidal gold) being absorbed to a greater degree than larger ones 134, 135. Studies with highly insoluble radioactive metal NPs have shown extremely low transfer into blood following GI tract exposures,125, 136 but with some evidence that a negative surface charge promotes the absorption of the smallest particles 137. Electron microscopy with elemental analysis has identified nanosized particulates in liver, kidney, and colon tissue samples from humans 138–140.…”
Section: Nanoparticle Fate Following Contact With Epithelial Barriersmentioning
confidence: 99%